International society of sport psychology position stand: mental health through occupational health and safety in high performance sport - Schinke, R. J.; Giffin, C.; Cosh, S.; Douglas, K.; Rhind, D.; Harwood, C.; Si, G.; Papaiounnou, A. (International Journal of Sport and Exercise Psychology, 2021)
There is considerable attention devoted to athlete mental health in high-performance sport. The International Society of Sport Psychology seeks to extend this discourse by expanding the discussion through a lens of occupational health and safety (OHS). Drawing upon knowledge from OHS, the authors have considered existing mental health challenges as well as proactive and reactive strategies conducive of athlete safety. This Position Stand is structured into four sections. The authors introduce OHS and its relevance to high-performance sport in section one. Section two focuses on athlete mental health and the need for an OHS approach within sport organisations. Section three is focused particularly on athlete safety in relation to high-performance youth athletes. The fourth and final section is a broader ideological discussion of how OHS might vary in approach based on national sport systems and cultural orientation.